ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI MINAT BELAJAR SISWA - Darmawati, Darmawati; Wahyuddin, Wahyuddin; Mahmud, Randy Saputra (INSPIRAMATIKA, 2022)
This study aims to determine how the ability to solve mathematical problems in terms of the learning interest of class VIII students of SMP Negeri 18 Selayar Islands. The type of research used is descriptive-qualitative. The research subjects consisted of 3 students of class VIII B SMP Negeri 18 Selayar Islands which consisted of 1 student with high learning interest, 1 student with moderate learning interest, and 1 student with low learning interest. Data collection techniques used were questionnaires, mathematical problem solving ability tests, and interviews. The questions used to measure mathematical problem solving skills are in the form of essay questions totaling 2 numbers with a system of two-variable linear equations. The results of tests and interviews were analyzed based on indicators of mathematical problem solving ability, namely understanding problems, planning solutions, solving problems according to plan, and re-examining procedures and settlement results. good, at the stage of solving the problem according to the plan the subject is able to solve the problem well, and is able to re-examine the answer. returning to the procedure and the results of the completion of the subject did not re-examine the answer. Subjects with low learning interest understood the problem well, but were at the stage of planning the solution, solving the problem according to plan, and re-examining the procedure and the results of the investigation. settlement has not been fulfilled.